Molecular Simulation of H2O Adsorption in Mg-MOF-74 - Adhikari, Bishwas; Subedi, Anup; Bhusal, Aabiskar; Adhikari, Kapil (Journal of Engineering and Sciences, 2024)
Amidst a global challenge of increasing water scarcity, atmospheric water harvesting (AWH) has surfaced as a hopeful solution. Metal-organic frameworks (MOFs) are highly esteemed among porous materials for their wide-ranging use in the field of water adsorption. This study specifically focuses on investigating the water adsorption capacity of Mg-MOF-74. A hybrid GCMC/MD simulation in LAMMPS was employed to study the water uptake with respect to pressure at a constant temperature of 298 K, the adsorption site of water in the framework, and the interaction energy between them. The end results suggest that Mg-MOF-74 exhibits promising potential as an effective adsorbent for atmospheric water harvesting, boasting a decent uptake of 25.172 mmol/g even at a low pressure of 1 bar. Furthermore, radial distribution function (RDF) analysis reflects the importance of the open metal site in the framework, closer to which the adsorbed water molecules can be seen. Water uptake increases as the pressure increases, which decreases the diffusion coefficient. At the same time, the interaction energy between water and the framework becomes more and more negative with an increase in pressure.